2017
DOI: 10.3892/mmr.2017.8126
|View full text |Cite
|
Sign up to set email alerts
|

Retinal microvasculature alteration in central serous chorioretinopathy

Abstract: The aim of the present study was to investigate the changes of retinal microvascular network in patients with central serous chorioretinopathy (CSCR). A total of fifteen patients (right eye) with CSCR and 15 normal controls (right eye) were recruited. We used optical coherence tomography angiography to scan 6×6 mm macular retinal blood flow images with the application of a series of customized image segmentation processing program software to obtain microvascular and macrovascular density, and compared the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
2
15
1
Order By: Relevance
“…The higher disruption presence of EZ ( p < 0.01) in chronic CSC could also be a piece of evidence to sustain the injury on DCP. Though Yu et al [12] had found a decreased superficial microvascular density and the superficial total microvascular density in acute CSC patients (15 eyes), there was no statistical difference between acute CSC and controls in our study. Depending on the good vision and fine configuration, we propose that the progression of decreasing blood flow is gradual, which may not be presented in an acute course.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The higher disruption presence of EZ ( p < 0.01) in chronic CSC could also be a piece of evidence to sustain the injury on DCP. Though Yu et al [12] had found a decreased superficial microvascular density and the superficial total microvascular density in acute CSC patients (15 eyes), there was no statistical difference between acute CSC and controls in our study. Depending on the good vision and fine configuration, we propose that the progression of decreasing blood flow is gradual, which may not be presented in an acute course.…”
Section: Discussioncontrasting
confidence: 95%
“…Furthermore, Lee et al [11] described that the FAZ expanded as diabetic retinopathy progresses. Notably and rarely in a CSC study, Yu et al [12] calculated the VD of 15 CSC patients (within 1 month of symptom onset) and 15 controls in 6 × 6 mm OCTA images. The results turned out that VD of a 3-mm macular ring area decreased significantly and had a positive correlation with VA.…”
Section: Introductionmentioning
confidence: 99%
“…2). Images showing subretinal hyperreflective material or pigment epithelial detachment (PED) in the macular area were excluded, as these overlying structures can be associated with shadow artefacts at the level of choriocapillaris OCTA [18][19][20][21][22]. Low-quality OCTA images related to improper centring, movement artefacts, or a signal strength less than 6 were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…OCTA imaging of CSC has permitted us to better delineate some aspects of the choroidal circulation, such as abnormal choriocapillaris and choroid flow patterns [17,18], not only in CSC eyes but also in fellow eyes without serous retinal detachment [19], and dark areas and dark spots observed in the choriocapillaris [17,18], which have been interpreted as possible focal flow reductions that should be distinguished from possible imaging artefacts [19,20]. Moreover, inner retinal microvasculature alterations in the macular region have been described [21].…”
Section: Introductionmentioning
confidence: 99%
“…A multicenter case-control study of 35 patients with CSCR and 25 age-matched controls showed increased choriocapillaris vascular density during stress in CSCR patients compared to controls, although the former had lower baseline values ( p < 0.05). 81 Yu and colleagues 82 also demonstrated a decrease in superficial total microvasculature in CSCR compared to controls in 15 patients using a customized image segmentation processing program to analyze 6 × 6 mm macular retinal blood flow OCTA images.…”
Section: Fafmentioning
confidence: 99%